High-resolution community analysis of deep-sea copepods using MALDI-TOF protein fingerprinting. (August 2018) - Kaiser, Patricia; Bode, Maya; Cornils, Astrid; Hagen, Wilhelm; Arbizu, Pedro Martínez; Auel, Holger; Laakmann, Silke
Abstract: Knowledge of zooplankton community structure is essential to understand ecosystem functioning. Therefore, accurate species identification is a crucial step in plankton studies. Yet, with the current array of methodologies, species richness is still largely underestimated and high-resolution distribution patterns remain unknown. A novel, cost-effective and rapid alternative to morphological or genetic approaches is the identification of species by proteomic fingerprinting based on matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). The present study aims to demonstrate the applicability of proteomic fingerprinting for large-scale identification and quantification of the pelagic copepod family Spinocalanidae. Therefore, MALDI-TOF MS was applied to discriminate, identify and quantify adult and juvenile planktonic copepods of the ecologically important deep-sea copepod family Spinocalanidae from stratified depth samples (0–1000 m) at two stations in the eastern tropical Atlantic. Spectral peak data from 1178 spinocalanid specimens of all developmental stages were compared with a reference library of previous proteomic fingerprints of genetically and morphologically identified spinocalanid species. A comparison with the library yielded 25 valid species clusters, which were used to create fine-scale vertical distribution profiles with a high species and stage resolution. Further, we were able to show vertical habitat partitioning among cryptic species and developmental stages, which has major consequences for our understanding of niche partitioning of the mesopelagic realm. Thus, proteomic fingerprinting holds great potential in accelerating and improving community analysis, providing a powerful tool to obtain new insights into biodiversity processes, phylogeographic patterns and mechanisms of vertical distribution. Highlights: Proteomic fingerprinting is an efficient and reliable tool for species identification. Proteomic fingerprinting proved its potential for biodiversity and ecology research. New information on copepod species- and stage-specific distribution patterns. Vertical habitat partitioning plays a major role in cryptic speciation.